Invisible Mothers: Unseen yet Hypervisible After Incarceration. By Garcia-HallettJanet (University of California Press, 2022, 248pp. £30.00) - Michalsen, Venezia (The British Journal of Criminology, 2023)
Invisible Mothers: Unseen yet Hypervisible After Incarceration, the new book by Dr. Janet Garcia-Hallett, has almost innumerable contributions to the field. The first thing that the reader will likely notice that makes this work stand out is the impact of Garcia-Hallett’s positionality as an Afro-Latina mother on the holistic understanding of the experiences of the Black and brown women as mothers and victims of the racist American carceral system. Garcia-Hallett grew up in Harlem, witnessing the transformation of her community due to the takeover of the penal system. For this book, she interviewed 37 mothers in New York City with histories of incarceration, and her writing skilfully puts the reader in her shoes as she presents the findings from her interviews, which took place in their kitchens, booths in McDonald’s, and at tables in shelters. In her exploration of these women’s experiences, Garcia-Hallett departs from the traditional pitiful exploration of their lives, but instead, paints a complicated, multifaceted picture of women engaging actively in many different types of motherwork, while facing almost constant obstacles from racist and misogynist criminal legal and child welfare systems that criminalize, pathologize and penalize their survival of their marginalization, rather than helping ‘save’ children and their mothers. She provides a critical and structural analysis while also introducing each woman as deeply unique in her strengths and challenges and is able to acknowledge the importance of the children without letting them overshadow the mothers. This is no small feat.
Keywords: book.review; dept.soc